Structure, stability, and IgE binding of the peach allergen Peamaclein (Pru p 7). Issue 5 (September 2014) - Tuppo, Lisa; Spadaccini, Roberta; Alessandri, Claudia; Wienk, Hans; Boelens, Rolf; Giangrieco, Ivana; Tamburrini, Maurizio; Mari, Adriano; Picone, Delia; Ciardiello, Maria Antonietta
ABSTRACT Knowledge of the structural properties of allergenic proteins is a necessary prerequisite to better understand the molecular bases of their action, and also to design targeted structural/functional modifications. Peamaclein is a recently identified 7 kDa peach allergen that has been associated with severe allergic reactions in sensitive subjects. This protein represents the first component of a new allergen family, which has no 3D structure available yet. Here, we report the first experimental data on the 3D‐structure of Peamaclein. Almost 75% of the backbone resonances, including two helical stretches in the N‐terminal region, and four out of six cysteine pairs have been assigned by 2D‐NMR using a natural protein sample. Simulated gastrointestinal digestion experiments have highlighted that Peamaclein is even more resistant to digestion than the peach major allergen Pru p 3. Only the heat‐denatured protein becomes sensitive to intestinal proteases. Similar to Pru p 3, Peamaclein keeps its native 3D‐structure up to 90°C, but it becomes unfolded at temperatures of 100–120°C. Heat denaturation affects the immunological properties of both peach allergens, which lose at least partially their IgE‐binding epitopes. In conclusion, the data collected in this study provide a first set of information on the molecular properties of Peamaclein. Future studies could lead to the possible use of the denatured form of this protein as a vaccine, and of the inclusion of cooked peach in the diet of subjects allergic to Peamaclein. © 2014 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 102: 416–425, 2014.